1999
DOI: 10.1584/jpestics.24.197
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 Biodiversity and Plant Protection

Abstract: Cytochrome P450 monooxygenases play an important role in detoxification and/or activation of xenobiotics including agrochemicals as well as in the modes of action of agrochemicals including fungicides, plant growth regulators, insecticide synergists and herbicide safeners. Current genome sequencing revealed that P450 genes are distributed into the five kingdoms of life: bacteria, protoctista, plants, animals and fungi, and a large number of P450 genes occur in animal and plant species. Particularly, Arabidopsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Xenobiotics, such as pesticides, in plants are catalyzed by xenobiotic-metabolizing enzymes, such as cytochrome P450. Ohkawa et al [28] reviewed the works for P450 and they suggested that over 360 of P450 had been found in plants by 1999, and their function was still in the process of being identified. For example, CYP76B1 from Helianthus tuberosus has the characteristic of oxidizing several phenylurea herbicides.…”
Section: Differences In Dieldrin-uptake Property Between Plantsmentioning
confidence: 99%
“…Xenobiotics, such as pesticides, in plants are catalyzed by xenobiotic-metabolizing enzymes, such as cytochrome P450. Ohkawa et al [28] reviewed the works for P450 and they suggested that over 360 of P450 had been found in plants by 1999, and their function was still in the process of being identified. For example, CYP76B1 from Helianthus tuberosus has the characteristic of oxidizing several phenylurea herbicides.…”
Section: Differences In Dieldrin-uptake Property Between Plantsmentioning
confidence: 99%
“…The patterns of expression of detoxifying enzyme-coding genes at various stages of growth and development and in various tissues can, to a certain extent, reveal the functions of genes ( Chung et al, 2009 ). These distinct expression patterns indicate that the proteins are involved in pesticide resistance and breakdown of secondary plant compounds ( Ohkawa et al, 1999 ). Similarly to the findings of previous research ( Xu et al, 2018 ; Hou et al, 2021 ), our findings revealed that MusiDN2722 is expressed in both larvae and adults.…”
Section: Discussionmentioning
confidence: 99%
“…Conjugates are actively transported to the vacuole and, in some cases, to the apoplast by the action of an ATP-dependent membrane pump [125][126][127]. Dihydroxylated pollutants can also be covalently linked with plant cell-wall polymers and lignin [128,129], probably through the action of cell-wall-or vacuole-associated enzymes (i.e., internal peroxidases and laccases). These enzymes, normally involved in the detoxification of H 2 O 2 , have been also associated with the formation of tyrosine or ferulate cross-links between different plant cell wall polymers with the non-specific oxidative polymerization of phenolic units to produce lignin and with the deposition of aromatic residues of suberin on the cell wall [130].…”
Section: Detoxification Of Organic Compoundsmentioning
confidence: 99%